Pendekatan Komprehensif Kesesuaian Lahan Budidaya Tanaman Padi Sawah di Kabupaten Paser, Provinsi Kalimantan Timur - Ngadisih Ngadisih; Lely Fitriana; Sahid Susanto; Sigit Supadmo Arief; Muhamad Khoiru Zaki; Chandra Setyawan (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
This study aimed to present a comprehensive evaluation of land suitability for wetland paddy cultivation in Paser Regency, East Kalimantan Province using the Simple Additive Weighting (SAW) process and Geographic Information System (GIS) techniques. The ten factors determining land suitability selected were soil texture, soil depth, soil drainage, soil type, rainfall, temperature, slope, distance from roads, distance from rivers and land use. The factor weights were considered the same, for the suitability analysis of the use of rice development in the study area. Then, after carrying out a weighted sum analysis, Paser Regency was qualitatively categorized as very suitable, quite suitable, marginally suitable, not currently suitable for rice land development with values ​​of 20, 39, 28, 13% respectively. Meanwhile, taking into account land use, the very suitable category was 20% and quite suitable was reduced to 33% of the total research area. Based on the available land, the opportunity for developing rice plantations in Paser Regency was relatively large. The study revealed that the SAW approach technique was acceptable for identifying appropriate land for rice development in the study area.